2016
DOI: 10.1007/s13361-016-1455-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of N-Succinylation of L-Lysylphosphatidylglycerol in Bacillus subtilis Using Tandem Mass Spectrometry

Abstract: Abstract. Phospholipids generally dominate in bacterial lipids. The negatively charged nature of phospholipids renders bacteria susceptible to cationic antibiotic peptides. In comparison with Gram-negative bacteria, Gram-positive bacteria in general have much less zwitterionic phosphatidylethanolamine. However, they are known for producing aminoacylated phosphatidylglycerol (PG), especially positively charged L-lysyl-PG, which is catalyzed by lysyl-PG synthase MprF, which appears to have a broad range of speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Proteomics is a recently developed powerful approach for investigating protein PTM sites (22)(23)(24). Here, we combined high-affinity purification with high sensitivity mass spectrometry technologies to identify the entire succinylome of A. hydrophila ATCC7966.…”
Section: Integrated Succinylome and Metabolome Profiling Reveals Crucmentioning
confidence: 99%
“…Proteomics is a recently developed powerful approach for investigating protein PTM sites (22)(23)(24). Here, we combined high-affinity purification with high sensitivity mass spectrometry technologies to identify the entire succinylome of A. hydrophila ATCC7966.…”
Section: Integrated Succinylome and Metabolome Profiling Reveals Crucmentioning
confidence: 99%
“…32 For example, the LysPGS from Agrobacterium tumefaciens and the AlaPGS from C. perfringens specifically use Lys-tRNA and Ala-tRNA respectively, while the aaPGS from Bacillus subtilis utilizes both Lys- and Ala-tRNA as amino acid donors in vitro . 32 Interestingly both Lys-PG and Ala-PG were initially detected in the membrane of B. subtilis , 33 but a recent report suggests that D-Ala-PG and not L -Ala-PG is formed in B. subtilis by an aaPGS independent pathway. 34 One paralog in Enterococcus faecium (referred to as RakPGS or MprF2) displays a more relaxed specificity for its aa-tRNA and can utilize Ala-, Lys-, and Arg-tRNAs.…”
Section: Aapgs Mediated Lipid Remodeling Uses Several Aa-trnas As Submentioning
confidence: 99%
“…A recent report showed that Lys-PG in B. subtilis is used to produce N-succinylated Lys-PG. 33 The biologic significance of and enzyme responsible for this modification are not known. However, it was proposed that a homolog of the enzyme responsible for protein succinylation, recently discovered in bacteria, may be accountable for Lys-PG modification.…”
Section: Homeostasis and Utilization Of Aa-pg In The Membranementioning
confidence: 99%
“…Small amounts of lysyl-DAG were detected in S. epidermidis lipids by a neutral loss scan for 146 amu lysine in positive mode (supplementary data). S. haemolyticus , however, produced N-succinyl-lysyl-PG as described previously 22 . In both lipidomes, PG was the predominant species followed by lysyl-PG, DGDG, and DAG (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…subtilis 21 . An ampicillin-resistant bacterium that produced N-succinyl-lysyl-phosphatidylglycerol 22 was identified as S . haemolyticus , a species that drew immediate attention to other Staphylococci pathogens.…”
Section: Introductionmentioning
confidence: 99%